Presidential Decree-Law No. 77 of the Year 2013 On Amending Some Provisions of the Penal Code - egypt (2025)
Presidential Decree-Law No. 77 of the year 2013 on amending some provisions of the penal code قرار رئيس جمهورية مصر العربية بالقانون رقم 77 لسنة 2013 فى شأن تعديل بعض أحكام قانون العقوبات